1999
DOI: 10.1111/j.1755-6686.1999.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood recirculation in malfunctioning catheters for haemodialysis

Abstract: Venous catheters are increasingly used for chronic haemodialysis, with dual lumen catheters being the most commonly used as blood recirculation (REC%) is relatively low. The aim of this study was therefore to evaluate blood recirculation in dual lumen catheters, both well-functioning and malfunctioning, with reversed lumens. In our study, blood recirculation in well-functioning catheters with standard lumens is similar to that found in previous studies. However, when lumens are reversed, blood recirculation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The degree of REC found in the totality of the catheters in this study is similar to that published in other works (3)(4)(5)(6). When the closely linked variables were related, a strong correlation was found between the drop in pre-pump pressure in the arterial line and the drop in real blood flow (Figure 1), which is logical given that the deviation of real blood flow with regard to theoretical flow depends directly on the drop of pressure in the arterial line.…”
Section: Discussionsupporting
confidence: 91%
“…The degree of REC found in the totality of the catheters in this study is similar to that published in other works (3)(4)(5)(6). When the closely linked variables were related, a strong correlation was found between the drop in pre-pump pressure in the arterial line and the drop in real blood flow (Figure 1), which is logical given that the deviation of real blood flow with regard to theoretical flow depends directly on the drop of pressure in the arterial line.…”
Section: Discussionsupporting
confidence: 91%
“…Previous small studies have reported that the prevalence of access recirculation (AR) ranges between 5% and 22% at conventionally prescribed blood flows, depending on catheter location and length and blood line position. [5][6][7][8][9][10][11][12][13][14][15] Although it is known that AR is more common in CVC than in arteriovenous accesses, the frequency of severe AR (Ͼ10%) is unknown, and the relation between AR, blood pump speeds (Q B ), and effective small solute clearance has not been previously described, to our knowledge.…”
mentioning
confidence: 99%
“…In well‐functioning catheters recirculation is typically negligible. When lumens are reversed, however, recirculation may be as high as 15% (14–16). Based on recommended guidelines, if recirculation exceeds 10% using the urea‐based method, investigation into the etiology should ensue (2).…”
Section: Definitionsmentioning
confidence: 99%